Development of low-emission photocatalytic cement composites with co-ground TiO₂–Fly Ash and TiO₂–calcium carbonate systems - Ślosarczyk , Agnieszka; Klapiszewska , Izabela; Jędrzejak , Patryk; Thomas , Marta; Klapiszewski , Łukasz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This study presents an innovative method for producing low-emission cement composites with photocatalytic properties by partially replacing Portland cement with fly ash, ground granulated blast furnace slag, and calcium carbonate. Novel ground systems combining fly ash-TiO2 or calcium carbonate-TiO2 were synthesized via high-energy ball milling to enhance dispersion and minimize TiO2 agglomeration. The modified composites exhibited improved hydration kinetics, including reduced setting times and up to 50% lower cumulative hydration heat. Mechanical tests confirmed comparable or superior compressive and flexural strengths as compared with the reference materials. All TiO2-containing composites showed UV-induced photocatalytic activity, with anatase-based systems yielding the best results. Carbon footprint analysis confirmed the environmental benefits, particularly in reducing CO2 emissions. These findingssupport the development of multifunctional, sustainable cementitious materials for eco-efficient construction.